Comparison of sleep and chronotype between senior and undergraduate university students. (2nd December 2019) - Núñez, P; Perillan, C; Arguelles, J; Diaz, E
ABSTRACT: The university programs for seniors provide a third age perspective in lifelong learning with classes and recreational facilities, and enable students to share their experiences and knowledge. A good sleep quality promotes better cognitive functioning and serves to protect against age-related cognitive declines. Central nervous system reorganization takes place during sleep, and although the influence of sleep quality on memory is not clear, circadian rhythm disorders affect alertness and individual performance. Physiological change during aging need to be clarified to better understand how university might help students. The aim of the present study was to evaluate for the first time the chronotype, the sleep quality and their relationship in senior university students and to compare them with those of undergraduate students. The Morningness–Eveningness Questionnaire ( MEQ ) and the Pittsburgh Sleep Quality Index ( PSQI ) were used. The results indicated that approximately 50% of the participants were good sleepers. This percentage was equal in the senior and undergraduate students. The results showed that undergraduate students tended toward eveningness while senior students tended toward morningness. Among the undergraduate students, evening type chronotypes had a tendency toward higher PSQI scores and this affected their daytime function scores, while it did not in the senior students, in whom worsening sleep quality was associated with disturbances such as going to the bathroom and nocturnal awakening. This information would be useful for designing environmental interventions to optimize sleep/work cycles for decreasing age-associated changes in memory in senior students and for improving the academic achievements of undergraduate students.